Influence of arching action on shear behaviour of laterally restrained concrete slabs reinforced with GFRP bars. (15th November 2015) - Zheng, Y.; Li, C.H.; Yang, J.B.; Sun, C.
Abstract: This paper reveals the influence of arching action on the shear behaviour of glass fibre reinforced polymer (GFRP) reinforced laterally restrained concrete slabs in bridge decks. A total of seventeen full-size one-way concrete slabs were constructed and tested in this study. Those restrained test slabs represents typical full-scale dimensions of a real bridge deck slab 400 mm wide by 2400 mm long and 200 mm deep. The test variables were lateral restraint stiffness, reinforcement configuration and concrete strength. The behaviour of test slabs was discussed and the influence of those structural parameters on the amount of arching action was evaluated by comparing the results of different specimens. The test results showed that increasing the arching effect resulted in shear failure mode and larger shear strength. The experimental shear strengths of the restrained test slabs were compared with some theoretical predictions in the literatures. The results indicated that those theoretical methods yielded high conservative predictions. A theoretical model that takes into account the effect of arching action in the shear-strength prediction was proposed by the writers. This method provided accurate and slightly conservative predictions.